(untitled) (Research, Society and Development, 2021)
Biochemical Oxygen Demand (BOD) is one of the key parameters for determining the quality of an aquatic environment in view of the concentrations of organic materials distributed in the water column. The traditional method (DBO520) presents major obstacles, but the biggest one is the time needed to obtain the results and the subsequent application of mitigation measures in possible impacted environments. The temperate climate, found European countries, was primarily responsible for the 20°C temperature setting and the 5 days of incubation to complete the analysis. However, tropical countries have completely different climatic dynamics, making it essential to have methods that suit the conditions imposed by the environment. Thus, in this study, we sought to reduce the time for determining the Biochemical Oxygen Demand, according to the climatic conditions of tropical countries, consequently raising the temperature (25ºC; 28ºC) of the incubation rates. The results demonstrated the effectiveness of the change to the incubation temperatures at 28ºC (p = 0.941; f = 0.07), demonstrating in a simple and concise way that the temperature increase can be applied to carry out the method in tropical environments.